Growth, Reduction, and Survival of Bacteria on Melon Types - Thao P. Nguyen; Michelle D. Danyluk; Keith R. Schneider (EDIS)
From 1990 to 2000, over 700 cases of foodborne illness were associated with outbreaks due to melon consumption in the U.S. and Canada. Even with efforts to educate industry and consumers of safe produce-handling practices, in the last decade there were still over 1,100 documented illnesses associated with melon consumption. This 45-page fact sheet highlights the research that has been done to provide insight on possible sanitation methods and their efficacy in decontaminating melon types of foodborne pathogens as well as natural microflora. Written by Thao P. Nguyen, Michelle D. Danyluk, and Keith R. Schneider, and published by the UF Department of Food Science and Human Nutrition, May 2012.